Ultra-trace analysis of 36Cl by accelerator mass spectrometry: An interlaboratory study - Merchel,S; Bremser,W; Alfimov,V; Arnold,M; Aumaître,G; Benedetti,L; Bourlès,DL; Caffee,M; Fifield,LK; Finkel,RC; Freeman,SPHT; Martschini,M; et al. (Analytical and Bioanalytical Chemistry, 2011)
A first international 36Cl interlaboratory comparison has been initiated. Evaluation of the final results of the eight participating accelerator mass spectrometry (AMS) laboratories on three synthetic AgCl samples with 36Cl/Cl ratios at the 10-11, 10-12, and 10-13 level shows no difference in the sense of simple statistical significance. However, more detailed statistical analyses demonstrate certain interlaboratory bias and underestimation of uncertainties by some laboratories. Following subsequent remeasurement and reanalysis of the data from some AMS facilities, the round-robin data indicate that 36Cl/Cl data from two individual AMS laboratories can differ by up to 17%. Thus, the demand for further work on harmonising the 36Cl-system on a worldwide scale and enlarging the improvement of measurements is obvious. © 2011 Springer-Verlag.